TRANSFUSION TACTICS AND FREQUENCY OF DEVELOPMENT OF COMPLICATIONS OF THE LATE PERIOD IN THE INJURY OF THE BELLY AND RIB CAGE - Пелина, Наталья Александровна; Стяжкина, Светлана Николаевна; Аникин, Никита Николаевич (Medicine in Kuzbass, 2019)
The purpose of the study is to compare the results of treatment of victims in the conditions of early use of blood components (up to 12 hours after the injury) as well as at a later usage start. Material and methods. 103 cases of emergency surgical care for victims with injuries of abdomen and chest with the use of transfusion media were analyzed. All victims were subject to assessment of acute blood loss and dynamic assessment of the final total blood loss during the acute post-traumatic period. Blood volume in the body cavities was determined by non-invasive and invasive methods. Results. All victims recovered in different terms. The healing process was accompanied by the development of inflammatory, coagulopathic and destructive complications. Discussion. The volume of fluid in the cavities in the form of hemothorax or hemoperitoneum was strongly associated with the volume of the final total blood loss suffered by the victim and detected in 12 hours after the injury. The incidence of complications was less in patients treated with transfusion of blood components up to 12 hours after the injury than in those ones treated later on. Conclusion. An early start of transfusion of fresh frozen plasma in traumatic injury reduces the number of complications in the post-traumatic period.